The Influence of Academic Administration Services with the RATER Approach on Student Satisfaction in Higher Education - Farihah, Umi; Arifin, Samsul; Muhith, Abd.; Ghani, Muhammad Faizal A. (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze the influence of academic administration services, including Responsiveness, Assurance, Tangibility, Empathy, and Reliability (RATER), on student satisfaction at one of the State Islamic Religious Universities in East Java, Indonesia. A quantitative approach with an associative research type was used in this research. Sampling was conducted using a proportional random sampling technique, resulting in a sample of 109 students. Data was collected through a questionnaire tested for validity and reliability. Data analysis was carried out using multiple linear regression tests. The research results show that academic administration services, which include the RATER dimension, simultaneously influence student satisfaction. However, only three variables have a partial influence: responsiveness, assurance, and tangibility. These findings imply that improving the quality of academic administration services based on the RATER dimensions is needed to increase student satisfaction. This shows the potential for improving academic administration services in higher education, focusing on critical aspects such as Responsiveness, Assurance, Tangibility, Empathy, and Reliability (RATER) to increase student satisfaction and institutional reputation.